The behavior of Malaysian stock market: evidence from nonlinear unit root test - Abdul Manap, Turkhan Ali; Omar, Mohd. Azmi (2010)

(untitled)
This paper reexamines the efficient hypothesis using monthly Kuala Lumpur stock price data for the period January 1970 to August 2009, using the nonlinear unit root test procedure recently developed by Kapetanios et al. (2003) in addition to the linear unit root test with and without structural breaks. While the linear unit root tests could not reject the null of unit root at any conventional level of significance, the nonlinear unit root test rejects the null hypothesis of unit root, suggesting that Malaysian stock markets is not weak form efficient, which is contrary to the findings of other studies available in the literature. The estimated ESTAR models provide strong evidence that the Malaysian stock market is characterized by a slower speed of mean reversion process.